DNA Methyltransferase 3A Is Involved in the Sustained Effects of Chronic Stress on Synaptic Functions and Behaviors - Wei, Jing (Cereb Cortex, 2020)
Emerging evidence suggests that epigenetic mechanisms regulate aberrant gene transcription in stress-associated mental disorders. However, it remains to be elucidated about the role of DNA methylation and its catalyzing enzymes, DNA methyltransferases (DNMTs), in this process. Here, we found that male rats exposed to chronic (2-week) unpredictable stress exhibited a substantial reduction of Dnmt3a after stress cessation in the prefrontal cortex (PFC), a key target region of stress. Treatment of unstressed control rats with DNMT inhibitors recapitulated the effect of chronic unpredictable stress on decreased AMPAR expression and function in PFC. In contrast, overexpression of Dnmt3a in PFC of stressed animals prevented the loss of glutamatergic responses. Moreover, the stress-induced behavioral abnormalities, including the impaired recognition memory, heightened aggression, and hyperlocomotion, were partially attenuated by Dnmt3a expression in PFC of stressed animals. Finally, we found that there were genome-wide DNA methylation changes and transcriptome alterations in PFC of stressed rats, both of which were enriched at several neural pathways, including glutamatergic synapse and microtubule-associated protein kinase signaling. These results have therefore recognized the potential role of DNA epigenetic modification in stress-induced disturbance of synaptic functions and cognitive and emotional processes.